2015
DOI: 10.1002/pd.4622
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in the prenatal detection of critical congenital heart disease

Abstract: Objectives Prenatal diagnosis of critical congenital heart disease, that requiring surgical or catheter intervention in the first 30 days of life, allows for delivery at a specialized center which can reduce preoperative morbidity and mortality. We sought to identify risk factors for a missed prenatal diagnosis of critical congenital heart disease. Methods Patients presenting to the Children’s Hospital of Wisconsin with critical congenital heart disease from 2007-2013 were included. Those with a prenatal dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
97
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(103 citation statements)
references
References 28 publications
(49 reference statements)
2
97
1
3
Order By: Relevance
“…The antenatal detection achieved in this study is superior to rates reported by many other developed countries . This may be attributed to various factors.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…The antenatal detection achieved in this study is superior to rates reported by many other developed countries . This may be attributed to various factors.…”
Section: Discussioncontrasting
confidence: 84%
“…This relates to the relative simplicity of diagnosing single ventricle anomalies, that are associated with a guarded outlook, such as HLHS and TA by means of the four‐chamber view of the fetal heart. The presence of an extra‐cardiac or chromosomal anomaly also improves the likelihood of antenatal detection significantly, but the presence of these co‐morbidities is another poor prognostic indicator. A higher mortality rate was observed among those born before 37 weeks’ gestation.…”
Section: Discussionmentioning
confidence: 99%
“…Its routine application led to the detection of many forms of CHD and early incorporation into ultrasound practice guidelines. As a consequence, detection rates of > 85% have been achieved for four‐chamber pathologies, including hypoplastic left and right heart syndrome and complex cardiac pathology associated with heterotaxy syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in case mix between the most versus least deprived are one possible mechanism. In some populations, prenatal diagnosis of CHD is less common in those living in higher poverty . This may affect case mix if severe cases are undiagnosed and therefore more likely to continue to term in those of lower compared to higher SES.…”
Section: Commentmentioning
confidence: 99%